Nanoparticle–EMF synergism: a study on the combined effects on developmental and behavioral endpoints in Drosophila melanogaster - Bhandari, Manisha; Anand, Avnika Singh; Verma, Kalyani; Regmi, Karuna; Amitabh; Prasad, Dipti. N.; Kohli, Ekta (Frontiers in Public Health, 2025)
The accelerated progression of modern technologies has exponentially amplified the pervasive presence of electromagnetic fields (EMFs) and nanoparticles (NPs) in various environments, from military arsenals to domestic settings. Despite extensive research on individual exposures, the cumulative effect of EMF and NPs co-exposure on biological systems remains poorly understood. This study investigates the combinatorial effects of 2.4 GHz EMF and zinc oxide (ZnO) NP exposure on Drosophila melanogaster across subsequent generations. We assessed various biological endpoints, including longevity, motor-neuronal responses, oxidative stress response, memory and learning responses, and phenotypic abnormalities. Flies were exposed to 2.4 GHz EMF for 10, 20, and 30 min independently and in combination with 0.1 mM and 0.5 mM ZnO NPs through the ingestion method. Our results showed that exposure to EMF significantly increased fly survival from day 14 to 50 following 10 min, with a more pronounced and sustained effect observed at 20 min (from day 14 to end of cycle). Independent exposure to 0.1 mM ZnO NPs had no observable effect on survival, whereas 0.5 mM NPs showed a steep decline from day 7. However, coexposure with 20-min EMF improved survival ability, inducing longevity from day 17 to 32 with 0.1 mM ZnO NPs, and from day 14 to 39 with 0.5 mM ZnO NPs. Behavioral impairments, elevated oxidative stress, and declined memory and learning abilities were observed. Furthermore, tergite patterning and pigmentation abnormalities were induced by EMF exposure, which were reversed over the subsequent generations. These findings highlight the complex, dose- and time-dependent biological responses to combined EMF and NP exposure. Our study emphasizes the need for further investigation into the potential risks and applications of these combinatorial interactions.